Herbicide Phosphinothricin Causes Direct Stimulation Hormesis - Milan Dragićević; Jelena Platiša; Radomirka Nikolić; Slađana Todorović; Milica Bogdanović; Nevena Mitić; Ana Simonović (SAGE Publishing, 2013)
Herbicide phosphinothricin (PPT) inhibits glutamine synthetase (GS), a key enzyme in nitrogen assimilation, thus causing ammonia accumulation, glutamine depletion and eventually plant death. However, the growth response of Lotus corniculatus L. plants immersed in solutions with a broad range of PPT concentrations is biphasic, with pronounced stimulating effect on biomass production at concentrations ≤ 50 μM and growth inhibition at higher concentrations. The growth stimulation at low PPT concentrations is a result of activation of chloroplastic isoform GS2, while the growth suppression is caused by inhibition of both cytosolic GS1 and GS2 at higher PPT concentrations. Since the results are obtained in cell-free system (e.g. protein extracts), to which the principles of homeostasis are not applicable, this PPT effect is an unambiguous example of direct stimulation hormesis. A detailed molecular mechanism of concentration-dependent interaction of both PPT and a related GS inhibitor, methionine sulfoximine, with GS holoenzymes is proposed. The mechanism is in concurrence with all experimental and literature data.